Antibiotic Sensitivity of Pathogens Causing Urinary Tract Infection (Bangladesh Pharmaceutical Journal, 2013)
Diagnosis of urinary tract infection (UTI) causing pathogens with their sensitivity to different antibiotics was performed with a total of 96 samples from both male (n=31; 32.3%) and female (n=65; 67.7%) of different age groups. Out of 96 urine samples, 55 (57.3%) were found positive after culturing in MacConkey agar plates. The percent distribution of positive cases against collected samples was higher for female (67%) than male (32%). However, female and male at the reproductive age of 16-30 years were more susceptible to UTI. A total of 55 bacterial isolates were identified by conventional methods and their antibiotic sensitivity was tested using Mueller- Hinton agar plates. The predominant isolates were Escherichia coli (34.5%), Klebsiella sp. (18.2%) and Staphylococci (20.0%). The sensitivity pattern for most of the isolated organisms showed 50% and/or higher sensitivity to imipenem, azithromycin and cephalexin, except Staphylococci (only 9.09% to azithromycin). DOI: http://dx.doi.org/10.3329/bpj.v16i1.14491 Bangladesh Pharmaceutical Journal 16(1): 53-58, 2013